Disseminated histoplasmosis mimicking an acute appendicitis - Marzukie, Marsilla Mariaty; Ahmad Affandi, Khairunisa; Yahaya, Azyani; Periyasamy, Petrick (Malaysian Society of Pathologists, 2019)
Introduction: Histoplasmosis can present in a myriad of clinical manifestations, which often makes its diagnosis difficult and occasionally, deceptive. Case Report: We describe a case of a 33 years old gentleman who was clinically diagnosed as acute appendicitis at initial presentation in view of a one-week history of fever, right lower quadrant abdominal pain- and guarding at right iliac fossa. He had thrombocytopenia and lymphopenia on presentation. Mesenteric lymphadenitis and small bowel lesion were found intraoperatively, which was respectively biopsied and resected. Histopathological result confirms disseminated histoplasmosis. Retroviral screen was positive. He was treated with amphotericin B for one week, subsequently switched to oral itraconazole, followed by initiation of highly active antiretroviral therapy (HAART). Discussion: This case illustrates the various nature of histoplasmosis presentation. A high index of suspicion is needed to clinch the diagnosis and subsequently institute prompt treatment as disseminated disease can be fatal if left untreated in an immunosuppressed host.